Alih Kode dan Campur Kode pada Akun Instagram @Londokampung: Kajian Sosiolinguistik - Yuni Arta Yuda Wicaksana; Udjang Pairin M. Basir; Yuniseffendri Yuniseffendri (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to explore the forms of language variants in the form of types of sociolect, diction, code switching and code mixing which is used on the Instagram account @Londokampung. This is qualitative research and the research data was taken from transcripts of conversations in videos uploaded to the Instagram account @Londokampung. Furthermore, based on analysis of the transcript data obtained, there are forms of code switching and code mixing used in conversations in videos on the Instagram account @Londokampung. The form of code switching is in the form of a regional language, namely Javanese, with a foreign language, namely English. Meanwhile, based on the data that has been found and collected, there is a form of code mixing that is used, namely in the form of language insertion using regional languages, namely Javanese and also foreign languages, namely English and using Indonesian.